DAMPAK IMPLEMENTASI KEBIJAKAN LOOK EAST DAN ACT EAST INDIA TERHADAP HUBUNGAN INDIA DAN ASEAN - Luluk Fadilah; Anggy Wira Pambudi (Universitas 17 Agustus 1945 Jakarta, 2020)
This study discusses how the impact of the Look East and East Act policies implemented by the Government of India in establishing foreign relations. Specifically, this study will examine the effect caused by the Look East policy and the Act East policy implemented by the Government of India on India-ASEAN relations. This research will use the Balance of Power theory to explain the political factors in Look East and Act East policies. Another theory that will also be used is the concept of regionalism which will be used to explain efforts to expand India's influence into the ASEAN region through the Look East and East Act policies. This research has found that the Look East and East India Act policies have an impact on India and ASEAN relations such as in the fields of economy and trade